Cover Picture: Aminobenzimidazoles and Structural Isomers as Templates for Dual‐Acting Butyrylcholinesterase Inhibitors and hCB2R Ligands To Combat Neurodegenerative Disorders (ChemMedChem 12/2016). (21st June 2016) - Dolles, Dominik; Nimczick, Martin; Scheiner, Matthias; Ramler, Jacqueline; Stadtmüller, Patricia; Sawatzky, Edgar; Drakopoulos, Antonios; Sotriffer, Christoph; Wittmann, Hans‐Joachim; Strasser, Andrea; Decker, Michael
Abstract : The front cover pictures shows a benzimidazole‐based lead structure that acts as both an inhibitor of butyrylcholinesterase (above) and a ligand for the human cannabinoid receptor 2 (below). Such dual‐acting compounds targeting both an enzyme and a G protein‐coupled receptor represent lead structures of drug candidates for neurodegenerative disorders like Alzheimer's disease. By compound library synthesis, second generation lead structures such as 2‐aminobenzimidazoles were discovered as dual‐acting compounds with low‐micromolar inhibition constants on both targets. The binding modes obtained by docking and molecular dynamics techniques helped to rationalize this mode of action. More information can be found in the Full Paper by Michael Decker et al. onpage 1270 in Issue 12, 2016 (DOI:10.1002/cmdc.201500418 ). (Artwork components used with permission from Shutterstock: Hubis/Tony Sanchez.)